(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Sexual assault is about the most dehumanizing form of gender based violence against women worldwide. Nigeria and many other countries in Africa do not have National data on women sexual assault. This survey is aimed at generating data on sexual assault against women in Osun state, Nigeria. Objective: To determine the patterns of sexual assault against women in Urban and Rural areas of Osun State in South western Nigeria. Methodology: A cross section survey using interviewer administered questionnaire was carried out among selected 1,200 women aged 15 years and above in urban and rural areas, between August and December 2014. The questionnaire was patterned after WHO Multi-country study on women’s health and domestic violence data instrument. The data were analyzed using SPSS version 17.0. Results: Mean age of the respondents was 23.75 ±(13.22) years in rural area, in the urban area it was 27.69 ±(10.23) years. 46 % and 54 % were married in urban and rural areas respectively. The prevalence of completed rape was 10.0 % in urban and 9.2 % in rural, while that of attempted rape was 31.4 % and 20.0 % in the urban and rural area respectively. Women in the rural areas experienced repeat sexual assault and suffered non-genital injuries more the in urban area. Having partner and living in urban area were associated with female sexual assault. Conclusions: Sexual assault against women constitutes public health issue in Osun state with rural women incurring greater negative health consequences. Primary prevention strategies should focus at young men and women in both rural and urban areas of the state. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.628-635